Public health nutrition from principles to practice - Lawrence, Mark; Worsley, Tony (Routledge, 2007)
Public Health Nutrition is an essential resource for public health practitioners, researchers and administrators, as well as students of nutrition, dietetics and public health wishing to obtain advanced and specialised competencies.